Characterization of the class IIa histone deacetylases substrate specificity - Kutil, Zsofia; Meleshin, Marat; Baranova, Petra; Havlinova, Barbora; Schutkowski, Mike; Barinka, Cyril (FASEB journal, 2022)
Class IIa histone deacetylases (HDACs) play critical roles in vertebrate development and physiology, yet direct evidence of their intrinsic deacetylase activity and on substrate specificity regarding the peptide sequence is still missing. In this study, we designed and synthesized a combinatorial peptide library allowing us to profile class IIa HDACs sequence specificity at positions +3 through -3 from the central lysine modified by the well-accepted trifluoroacetyl function. Our data revealed a strong preference for bulky aromatic acids directly flanking the central trifluoroacetyllysine, while all class IIa HDACs disfavor positively charged residues and proline at the +1/-1 positions. The chemical nature of amino acid residues N-terminally to the central trifluoroacetyllysine has a more profound effect on substrate recognition as compared to residues located C-terminally. These findings were validated by designing selected favored and disfavored peptide sequences, with the favored ones are accepted with catalytic efficacy of 75 000 and 525 000 M-1 s-1 for HDAC7 and HDAC5, respectively. Results reported here could help in developing class IIa HDACs inhibitors and also in the search for new natural class IIa HDACs substrates.
Keywords: Peptides; substrates; sequence specificity; Amino Acid Sequence; deacetylation; peptide library; Histone Deacetylase Inhibitors; histondeacetylasy; inhibitory histondeacetylas; Substrate Specificity; substrátová specifita; class IIa histone deacetylases; Histone Deacetylases; sekvence aminokyselin; peptidy